Antiferro quadrupolar ordering in Fe intercalated few layers graphene - Abu Jahid Akhtar; Abhisek Gupta; Dipankar Chakravorty; Shyamal K. Saha (AIP Advances, 2013)
The π electron cloud above and below the honeycomb structure of graphene causes each carbon atom to carry a permanent electric quadrupole moment which can attach any cation to impart interesting physical properties. We have synthesized Fe intercalated graphene structures to investigate tunable magnetic properties as a result of this chemical modification. An interesting antiferro quadrupolar ordering is observed which arises due to a coupling between magnetic dipole moment of Fe and electric quadrupole moment on graphene surface. In contrast to antiferromagnetic Neel temperature (TN), here the ordering temperature (TQ) increases from 35.5 K to 47.5 K as the magnetic field is raised upto 1 Tesla.